2000
DOI: 10.1038/sj.ijo.0801222
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of lipase inhibitor CT-II, an extract from edible herbs, Nomame Herba, on rats fed a high-fat diet

Abstract: OBJECTIVE: To investigate the inhibitory effects of CT-II, extract of Nomame Herba, on lipase activity in vitro and on obesity in rats fed a high-fat diet in vivo. DESIGN: The assay for the inhibitory effect of CT-II on lipase activity was performed by measuring released free fatty acids after the incubation of the medium with CT-II, porcine pancreatic lipase and triolein (experiment 1). In vivo experiments, lean rats or obese rats (570 ± 718 g) were fed a high-fat diet containing 60% fat with or without CT-II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 18 publications
7
53
0
5
Order By: Relevance
“…27) Plant materials like Cassia mimosoides (ethanol extract) and Salacia reticulate (water extract), which act as pancreatic lipase inhibitors, have been reported to suppress body weight gain in animal model. 28,29) Our previous data exhibited that the DOB down-regulates porcine pancreatic lipase activity to 57% at a concentration of 10 µg/mL in vitro. 8) In the present study, high-fat diet-induced obese mice treated with DOB (100 mg/kg body weight) elevated fecal lipid, TG, and TC output to 1.3-, 1.7-, and 1.4-fold of control, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…27) Plant materials like Cassia mimosoides (ethanol extract) and Salacia reticulate (water extract), which act as pancreatic lipase inhibitors, have been reported to suppress body weight gain in animal model. 28,29) Our previous data exhibited that the DOB down-regulates porcine pancreatic lipase activity to 57% at a concentration of 10 µg/mL in vitro. 8) In the present study, high-fat diet-induced obese mice treated with DOB (100 mg/kg body weight) elevated fecal lipid, TG, and TC output to 1.3-, 1.7-, and 1.4-fold of control, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The observed weight loss may have been due to loss of adipose/fat tissues as internal organs were not adversely affected. Yamamoto et al (2000) had reported that edible herbs often caused a reduction in body weight via reduction in fat mass. The observed weight loss may have arisen from a variety of pathways.…”
Section: Discussionmentioning
confidence: 99%
“…A lipase inhibitor which reduces fat digestion and thus absorption, is one of widely accepted approaches in decreasing calorie intake. [1][2][3] Simple inhibition of lipid digestion and absorption is a prerequisite, but it is not sufficient for a successful long-term control of obesity. 4 Therefore, a coordinated measure to either reduce the food intake efficiency or promote energy expenditure is desirable to achieve a long-term efficacy.…”
Section: Introductionmentioning
confidence: 99%